PENGARUH PERAN KELUARGA DALAM PENCEGAHAN DAN PENANGANAN PERILAKU AGRESIF PRE HOSPITAL PADA KLIEN ODGJ - wittin khairani; Septa Rahayu Noemperani (Jurnal Kesehatan Masyarakat, 2023)
ABSTRACTThe phenomenon of hypertension is a deadly silent killer, meaning that hypertension cannot directly kill the sufferer but can trigger complications, such as: the risk of heart attack, heart failure, stroke, and kidney failure.The family has a role or function to carry out nursing care practices, namely to prevent health problems or treat sick family members. Family is the closest person who can provide support, care and affection to family members who suffer from hypertension and have a history of inpatient and outpatient care.Objective: To determine the influence and differences in the role of the family before and after the effective self-management intervention for preventing complications in hypertensiveMethods: The study used a quasi-experimental design with a pre-test and post-test nonequivalent control group design. The study population was all patients who had a history of hypertension who visited the Kasihan I Health Center, Bantul, DI Yogyakarta from January to August 2022, with a total sample of 30 people, carried out by purposive sampling. The data collection instrument used a respondent characteristic questionnaire, and a questionnaire about knowledge of family roles with effective self-health management interventions for preventing complications in hypertensive patients Data were analyzed univariately and bivariately with q-square test (95% CI).Results: There is an influence in the form of an increase in the role of the family, seen from the difference in the average value from pretest to posttest only 0.7 in the respondents' answers. There is a difference from the pre-test value to the post-test value, seen from the significance of p = 0.000 (p <0.05) after being given treatment/intervention about the role of the family with effective self-management interventions towards preventing complications in hypertensive patientsConclusion :There are influences and differences after the intervention was carried out on respondents regarding the role of the family with self-health management interventions effective in preventing complications in hypertensive patients